Factors affecting HIV counselling and testing (HCT) in the provision of prevention of mother to child transmission (PMTCT) services among pregnant women in Kabwe, Central Province of Zambie - Chitambala, Cecilia (Stellenbosch : Stellenbosch University, 2013)
Thesis (MPhil)--Stellenbosch University, 2013.